The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/jobm.201500590
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of mimosine, 3, 4 DHP and 2, 3 DHP degrading bacteria from a commercial rumen inoculum

Abstract: The presence of the toxic amino acid mimosine in Leucaena leucocephala restricts its use as a protein source for ruminants. Rumen bacteria degrade mimosine to 3,4- and 2,3-dihydroxypyridine (DHP), which remain toxic. Synergistes jonesii is believed to be the main bacterium responsible for degradation of these toxic compounds but other bacteria may also be involved. In this study, a commercial inoculum provided by the Queensland's Department of Agriculture, Fisheries, and Forestry was screened for isolation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…Non-protein amino acids can be incorporated into protein chains leading to the formation of non-functional products that cannot be metabolised [ 98 ]. The presence of non-protein amino acids in fodder poses risks to livestock due to their potential toxicity and anti-nutritional properties [ 25 , 64 , 99 ]. There are ca.…”
Section: Rumen Microbial Detoxification Of Plant Toxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-protein amino acids can be incorporated into protein chains leading to the formation of non-functional products that cannot be metabolised [ 98 ]. The presence of non-protein amino acids in fodder poses risks to livestock due to their potential toxicity and anti-nutritional properties [ 25 , 64 , 99 ]. There are ca.…”
Section: Rumen Microbial Detoxification Of Plant Toxinsmentioning
confidence: 99%
“…Based on early studies, it was thought that mimosine detoxification would require synergism between a variety of rumen microorganisms, with Jones and Megarrity [ 15 ] demonstrating that there were a range of bacteria in the rumen able to degrade mimosine to 3,4-DHP. A number of bacteria have been isolated including Streptococcus lutetiensis , Clostridium butyricum , Lactobacillus vitulinus and Butyrivibrio fibrisolvens that are able to degrade mimosine to DHP [ 99 ]. Additional bacteria such as S. jonesii are required for the further breakdown of 3,4-DHP to 2,3-DHP which S. jonesii can further convert to unidentified non-toxic metabolites.…”
Section: Rumen Microbial Detoxification Of Plant Toxinsmentioning
confidence: 99%
“… 23 25 and Eucalyptus extract has terpenes, acylphloroglucinols, euglobals, etc. 26 and mimosine presence in case of Leucaena 27 . The control MFC-C achieved a steady-state after 40 days of operation, depicting a stable OV value of 292 ± 5 mV.…”
Section: Resultsmentioning
confidence: 94%
“…In other study systems, the GI microbiome has been directly shown to influence diet selection through a single identifiable secondary metabolite or toxin that can be broken down by known microbial species that inhabits an enlarged foregut. For instance, Australian cattle eat Leucaena leucocephala only when bacteria that degrade mimosine are introduced to the rumen [7,48]. Furthermore, when the foregut pouches of woodrats (Neotoma spp.)…”
Section: Discussionmentioning
confidence: 99%